When restorative justice meets the Good Lives Model: Contributing to a criminology of trust. (May 2021) - Walgrave, Lode; Ward, Tony; Zinsstag, Estelle
The Good Lives Model and restorative justice, although both innovative practices with a number of common traits, interests and aims, have been developing in parallel or even at odds with each other for a number of years. As a consequence, they have rarely been examined as possibly complementary and of use to each other. In this article we aim to explore these innovative practices individually and to look at how they might work together to address the harm in a positive and constructive way for all stakeholders. We examine the possibilities of how a new approach to criminology, a criminology of trust, could be further developed through their lens and their possible complementarity.